Sample agendas for an evaluability assessment stakeholder workshop (Methods Lab, 2015)
An evaluability assessment aims to assess the extent to which, and how best, an intervention can be evaluated in a reliable and credible fas hion. These sample agendas are intended for people convening key stake holders (such as project implementation staff and managers, donors and government officials) to discuss the purpose and scope of an impact e valuation and to identify key evaluation questions. This tool was deve loped by Bronwen McDonald, Anne Buffardi and Irene Guijt for use in Me thods Lab projects. It accompanies the Methods Lab publication ‘Evalua bility assessment for impact evaluation: guidance, checklists and deci sion support’.